Solar Modulation of Low-energy Cosmic-Ray Nitrogen and Its Comparison with Oxygen - Yun Li; Xiaoping Zhang; Shuai Fu; Zhenning Shen; Yi Xu; Haoyu Lu; Jinbin Cao; Tianle Zhu (The Astrophysical Journal)
The heliospheric environment is very complex and filled with diverse high-energy particles from various origins, and among these particles, cosmic rays (CRs), including anomalous and Galactic components (ACRs and GCRs), are unique as they originate from beyond the solar system. Due to their stable and long-lasting presence in the heliosphere, the study of CRs is crucial for protecting humanity and other lifeforms against the hazards of high-energy radiation. In this work, we aim to study the prolonged changes in CR nitrogen, a fundamental element that constitutes amino acids, using the measurements from the Advanced Composition Explorer (ACE) spacecraft. The comparison of solar modulation on CR nitrogen and oxygen is also made using the yearly averaged ACE observations. The ACR nitrogen has a more even spectrum than ACR oxygen while the spectrum of GCR nitrogen is more abrupt than GCR oxygen. Further model results indicate that GCR nitrogen and oxygen undergo comparable modulation processes within the heliosphere and the slight difference between the observed power-law indices of nitrogen and oxygen spectrum is due to the distinct local interstellar spectrum of the two species. Besides, an analysis is made to explain the observed more flattened ACR spectrum of nitrogen than oxygen caused by the slightly different charge-to-mass ratio Z / A .